UK AMD/DR EMR REPORT IX: comparative effectiveness of predominantly as needed (PRN) ranibizumab versus continuous aflibercept in UK clinical practice. Issue 12 (6th May 2017) - Lee, Aaron Y; Lee, Cecilia S; Egan, Catherine A; Bailey, Clare; Johnston, Robert L; Natha, Salim; Hamilton, Robin; Khan, Rehna; Al-Husainy, Sahar; Brand, Christopher; Akerele, Toks; Mckibbin, Martin; et al.
Abstract : Aims: To compare the effectiveness of continuous aflibercept versus pro re nata (PRN) ranibizumab therapy for neovascular age-related macular degeneration (nAMD). Methods: Multicentre, national electronic medical record (EMR) study on treatment naive nAMD eyes undergoing PRN ranibizumab or continuous (fixed or treat and extend (F/TE)) aflibercept from 21 UK hospitals. Anonymised data were extracted, and eyes were matched on age, gender, starting visual acuity (VA) and year of starting treatment. Primary outcome was change in vision at 1 year. Results: 1884 eyes (942 eyes in each group) were included. At year 1, patients on PRN ranibizumab gained 1.6 ETDRS (Early Treatment Diabetic Retinopathy Study) letters (95% CI 0.5 to 2.7, p=0.004), while patients on F/TE aflibercept gained 6.1 letters (95% CI 5.1 to 7.1, p=2.2e-16). Change in vision at 1 year of the F/TE aflibercept group was 4.1 letters higher (95% CI 2.5 to 5.8, p=1.3e-06) compared with the PRN ranibizumab group after adjusting for age, starting VA, gender and year of starting therapy. The F/TE aflibercept group had significantly more injections compared with the PRN ranibizumab group (7.0 vs 5.8, p<2.2e-16), but required less clinic visits than the PRN ranibizumab group (10.8 vs 9.0, p<2.2e-16). Cost-effectiveness analysis showed an incremental cost-effectiveness ratio of 58 047.14 GBP/quality-adjusted life year for continuous aflibercept over PRN ranibizumab. Conclusion: Aflibercept achieved greater VA gains at 1 year than ranibizumab. The observed VA differences are small and likely to be related to more frequent treatment with aflibercept, suggesting that ranibizumab should also be delivered by F/TE posology.